The Uncanny Child in Transnational Cinema : Ghosts of Futurity at the Turn of the Twenty-first Century - Balanzategui, Jessica (Book collections on Project MUSE., 2018)
Contents: The Child as Uncanny Other / Section One / Secrets and Hieroglyphs: The Uncanny Child in American Horror Film / Chapter One: The Child and Adult Trauma in American Horror of the 1980s / Chapter Two: The Uncanny Child of the Millennial Turn / Section Two / Insects Trapped in Amber: The Uncanny Child in Spanish Horror Film / Chapter Three: The Child and Spanish Historical Trauma / Chapter Four: The Child Seer and the Allegorical Moment in / Millennial Spanish Horror Cinema. / Section Three / Our Fear Has Taken on a Life of Its Own: The Uncanny Child in Japanese Horror Film / Chapter Five: The Child and Japanese National Trauma / Chapter Six: The Prosthetic Traumas of the Internal Alien in Millennial J-Horror / Section Four[-]Trauma's Child: The Uncanny Child in Transnational Remakes and Co-productions / Chapter Seven: The Transnational Uncanny Child/ Chapter Eight: Progress and Decay in the Twenty-first Century: The Postmodern Uncanny Child in The Others / Chapter Nine: 'Round and round, the world keeps spinning. When it stops, it's just beginning:' Analogue Ghosts and Digital Phantoms in The Ring.